Virtual Reality Behavior Change Interventions for Environmental Sustainability - Nirhamo, Eero (My University, 2026)
Climate change is a pressing issue where dominant research modes have not provided sufficient solutions for endeavors such as affecting sustainable behavior. Contemporary technological advances may provide new solutions when studied through multidisciplinary analysis. The use of virtual reality for this purpose has great potential, explored in this thesis as a medium for changing the behavior related to environmental sustainability of individuals and groups. In this thesis, an exploratory framework is created. This is done through an exploration and combination of three areas of research: sustainability communication, behavior change interventions, and virtual reality experiences. Guidelines are gathered from each area, which are analyzed for two and three-way synergies to find actionable items to form a framework usable for any experience combining the three areas of research. A step is taken in verifying the exploratory framework by reflecting on it through a pilot study. An intervention doubling as an infotainment virtual reality experience on fuel use in cruise ships is created using the framework. The practical functionality of the framework is reflected by its applicability in creating such an intervention, and by the degree of success attained by the intervention. Indicative results tell of the success of the intervention and the validity of the theory used to form it. The framework is found to be practically functional, and possible directions to iterate it further through more practical and literary studies are identified. The framework and its contributing research contribute to the scientific rigor with which the three areas of research can be studied, and in providing much needed actionable ways to further environmental sustainability.
Keywords: VR, Virtual Reality, XR, Extended Reality, Behavior Change, Behavior Change Intervention, Sustainability, Sustainability Communication, Environmental Sustainability, Maritime Industry, Cruise Ship